Toxicological risk assessment of chemicals a practical guide - Nielsen, Elsa (Informa Healthcare, 2008)
Unlike many existing books on toxicology that cover either toxicity of a particular substance or toxicity of chemicals on particular organ systems, "Toxicological Risk Assessment of Chemicals: A Practical Guide" lays out the principle activities of conducting a toxicological risk assessment, including international approaches and methods for the risk assessment of chemical substances. It illustrates each step in the process: hazard identification, a dose response assessment, and exposure assessment. The book also summarizes the basic concepts of interaction of chemicals in mixtures and discusses various approaches to testing such mixtures.
Keywords: Toxicology.; Toxicity testing.; Health risk assessment.; Environmental risk assessment.; elektronické knihy; electronic books